JIGSAW: Helping Students to Comprehend Linguistics Material in Introduction to Linguistics Class at English Department of STKIP PGRI West Sumatra - Perpisa, Lili (Universitas PGRI Sumatera Barat, 2015)
This study aims to improve students' understanding of linguistics by using a jigsaw strategy. It is constituted as a linguistic study about language in overall. Language is a communication tool for a person which has several systems. Thus, the language itself is important to be learned and understood, especially for the students of the language. Another reason is the existence of several phenomena that researchers have encountered in the classroom in English language courses of STKIP PGRI SUMBAR. The study of language that is learned is English or English linguistic. First, English is a foreign language which is not easy to be learned. The second, the material on this language is a complete knowledge that cannot be separated from one another. Meanwhile, the time provided only 2.5 hours per week. Students are expected to understand the concept of language, how to communicate, sounds, words, meanings and applications. Third problem is learning strategies used by lecturers. Lecturer asks students to learn in groups. Each group will present a different material each week. Then the others respond, causing discussion. This strategy is less effective against the student's understanding. Discussion only occurs for students who had studied. Most of them are just silent. Likewise, group presentations, it will dominate only one or two students. The others are just as followers. So in this study the researcher wants to apply the jigsaw to solve the above problems.Type of research is a Classroom Action Research. It would increase the students' understandings of linguistic of STKIP PGRI SUMBAR. Participants that would be used were the student of English at STKIP PGRI SUMBAR who were taking the course Introduction to Linguistics. The data were collected through observation would also be assisted by collaborator. The instruments to be used are notes, interviews, and tests. The data is analysed by classifying based on the characteristics. Then, the data would be interpreted to see whether the jigsaw can increase students' understanding of linguistics or not.